ANGGAWASTA: KESADARAN JIWA DALAM KEKAWIN DHARMA NISKALA - Ni Made Ari Dwijayanthi; I Kadek Widiantana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Anggawasta (Author), the Universe, and the Creator are the author's methods inKekawin Dharma Niskala to get unification with the universe through his work. Anggawastais the term to use represent author in the Kekawin Dharma Niskala. The focus of this researchis to reveal the form, function, meaning, and position of the author in text. Pierce's semiotictheory is used to interpret the signs in the kekawin.